Cu(II)‐Mediated C−C/C−O Bond Formation via C−H/C−C Bond Cleavage: Access to Benzofurans Using Amide as a Traceless Directing Group. Issue 1 (14th November 2019) - Yu, Shuling; Lv, Ningning; Liu, Zhanxiang; Zhang, Yuhong
Abstract: A copper‐mediated synthesis of 2, 3‐disubstituted benzofurans with the assistance of an 8‐aminoquinolyl auxiliary is described from readily available benzamides and benzoylacetonitriles. In this reaction, the C−C bond is successfully constructed via C−H activation, and C−O bond is subsequently formed at the original position of the amide group in a one‐pot manner. The amide directing group is detached simultaneously under the reaction conditions through C−C bond cleavage. Surprisngly, the distinct isoquinolinone products can be achieved by changing the reaction conditions using ammonia as amine source. Abstract :